Sociodemographic determinants of vaccination and willingness to pay for COVID-19 vaccines in Hungary, results of a cross-sectional online questionnaire - Zsuzsanna Beretzky; Valentin Brodszky (BMC Public Health, 2024)
Abstract Background Several different coronavirus disease (COVID-19) vaccines were authorized and distributed all over the world, including Hungary, but vaccination rates and acceptance of the different vaccines varied through 2021 and subsequent years. In Hungary Western vaccines and the Chinese and Russian vaccines were available in early 2021. Understanding preference and willingness to pay (WTP) for the COVID-19 vaccine could provide information for policy decision making to control the COVID-19 pandemic. We aimed to assess the socio-demographic factors influencing the COVID-19 vaccination and to analyse individual preferences for the available COVID-19 vaccines in Hungary. Methods A cross-sectional online questionnaire survey was conducted between 25–05-2021 and 08–06-2021 exploring the vaccine acceptance and WTP for vaccination in the Hungarian general population. To assess the preferences towards the different vaccines available in Hungary at the time of the study, we used a multi-step WTP task. Results Altogether 2,000 respondents filled out our survey, with the average age of 49.1 (SD = 15.3), out of whom 370 respondents (18.5%) stated that they already had a COVID-19 infection. Age above 65 years, male gender, higher level of education, higher income and residence in the capital or county seats were associated with a higher probability of vaccination. The average WTP ranged from 14.2 to 30.3 EUR for the different vaccine types. Conclusions Males, respondents with higher education and income stated a higher WTP value for all vaccines. Better socioeconomic status increased both vaccination coverage and willingness to pay for vaccines.